Program Studi Pendidikan Biologi, Universitas Negeri Malang, Malang - Ali Sadikin; Asni Johari; Lili Suryani (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2020)
Web-based interactive biology multimedia to support the learning of the revolution 4.0 era is not yet available to the fullest. The purpose of this research is to develop interactive biology-based website multimedia in the face of the industrial revolution 4.0. The research method used, namely research & development with ADDIE product development models that include the analysis, design, development, implementation, and evaluation stages. The research instruments used were interview transcripts, observation sheets, material and media expert questionnaires, and product trial questionnaires for 46 students. Qualitative data in the form of expert validator suggestions and comments were analyzed descriptively. Quantitative data is processed into interval data using a Likert scale. The results showed that website-based interactive multimedia biology was declared valid in the media aspect (90%, very good criteria),material aspects (87.5%, very good criteria), and attractiveness aspects (88%, very good criteria). The conclusion of this research, which is interactive multimedia based on website biology, is suitable for biology learning.